Magnetically directed antioxidant and antimicrobial agent: synthesis and surface functionalization of magnetite with quercetin - Shah, Syed Tawab; Yehye, Wageeh Abdulhadi; Chowdhury, Zaira Zaman; Simarani, Khanom (PeerJ, 2019)
Oxidative stress can be reduced substantially using nanoantioxidant materials by tuning its surface morphological features up to a greater extent. The physiochemical, biological and optical properties of the nanoantioxidants can be altered by controlling their size and shape. In view of that, an appropriate synthesis technique should be adopted with optimization of the process variables. Properties of magnetite nanoparticles (IONP) can be tailored to upgrade the performance of biomedicine. Present research deals with the functionalization IONP using a hydrophobic agent of quercetin (Q). The application of quercetin will control its size using both the functionalization method including in-situ and post-synthesis technique. In in-situ techniques, the functionalized magnetite nanoparticles (IONP@Q) have average particles size 6 nm which are smaller than the magnetite (IONP) without functionalization. After post functionalization technique, the average particle size of magnetite IONP@Q2 determined was 11 nm. The nanoparticles also showed high saturation magnetization of about 51-59 emu/g. Before starting the experimental lab work, Prediction Activity Spectra of Substances (PASS) software was used to have a preliminary idea about the biological activities of Q. The antioxidant activity was carried out using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay. The antibacterial studies were carried out using well diffusion method. The results obtained were well supported by the simulated results. Furthermore, the values of the half maximal inhibitory concentration (IC50) of the DPPH antioxidant assay were decreased using the functionalized one and it exhibited a 2-3 fold decreasing tendency than the unfunctionalized IONP. This exhibited that the functionalization process can easily enhance the free radical scavenging properties of IONPs up to three times. MIC values confirms that functionalized IONP have excellent antibacterial properties against the strains used (Staphylococcus aureus, Bacillus subtilis and Escherichia coli) and fungal strains (Aspergillus niger, Candida albicans, Trichoderma sp. and Saccharomyces cerevisiae). The findings of this research showed that the synthesized nanocomposite has combinatorial properties (magnetic, antioxidant and antimicrobial) which can be considered as a promising candidate for biomedical applications. It can be successfully used for the development of biomedicines which can be subsequently applied as antioxidant, anti-inflammatory, antimicrobial and anticancer agents. © 2019 PeerJ Inc.. All rights reserved.